2013
DOI: 10.1016/j.joa.2013.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic ventricular arrhythmia originating from the para‐Hisian area: Prevalence, electrocardiographic and electrophysiological characteristics

Abstract: Background We investigated the prevalence and the electrocardiographic and electrophysiological characteristics of ventricular arrhythmias (VAs) originating from the para‐Hisian area. Methods Among 250 patients with idiopathic VAs, 8 (3.2%) had an ablation site in the para‐Hisian region. For comparison with right ventricular (RV) para‐Hisian VAs (n=6), 27 patients with VAs originating from the posterior RV outflow tract (RVOT) were studied. Results Para‐Hisian VAs had an R wave in leads I and aVL. The VAs orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…The 12‐lead electrocardiography (ECG) showed tall R waves in I and aVL, in addition to a near‐QS pattern in V1, relatively narrow QRS waves in V1‐2, and a precordial transition zone between V3 and V4 (Figure ). All these findings strongly suggested that the PVCs originated from the right ventricular septum close to the His bundle …”
Section: Case Reportmentioning
confidence: 77%
See 1 more Smart Citation
“…The 12‐lead electrocardiography (ECG) showed tall R waves in I and aVL, in addition to a near‐QS pattern in V1, relatively narrow QRS waves in V1‐2, and a precordial transition zone between V3 and V4 (Figure ). All these findings strongly suggested that the PVCs originated from the right ventricular septum close to the His bundle …”
Section: Case Reportmentioning
confidence: 77%
“…All these findings strongly suggested that the PVCs originated from the right ventricular septum close to the His bundle. 1,2,4,[9][10][11] After informed consent was obtained, a cardiac electrophysiological study was performed with the patient fasting and not taking antiarrhythmic drugs. A 4-Fr hexapolar electrode catheter (Supreme ™ , St. Jude Medical, Inc) was positioned in the His bundle region.…”
Section: Case Reportmentioning
confidence: 99%
“…reported that the voltage ratio of leads II and III was 65% versus 97% in patients with RVOT VAs (P < 0.0001) . In another study comparing VAs from the parahisian region (n = 6) and posterior RVOT (n = 27), a greater R wave amplitude in lead I (1.15 ± 0.34 mV vs. 0.34 ± 0.18 mV, P = 0.001), a smaller R wave amplitude in the inferior leads (0.68 ± 0.23 mV vs. 1.58 ± 0.55 mV, P < 0.001), and a higher R wave amplitude ratio in leads II/III (4.2 ± 2.0 vs. 1.1 ± 0.2, P = 0.01) were the major ECG predictors of a parahisian origin . Other distinctive characteristics include a relatively narrow QRS duration, explained by the early engagement of the His Purkinje network, and an RSR’ or RR’ pattern in aVL, a finding that was present in 28.6% of our patients.…”
Section: Discussionmentioning
confidence: 94%
“…Poor tissue-catheter contact F I G U R E 3 Examples of PVCs with positive/negative (1-6) and negative/positive (7-9) discordance. Mapping showed origin from the parahisian region (1-3), RV moderator band (4-6), and ALPM (7)(8)(9). In comparison with parahisian PVCs, MB PVCs exhibited a wider QRS duration, later precordial transition, and higher prevalence of notching in the inferior leads [Color figure can be viewed at wileyonlinelibrary.com] limits power delivery and may induce frequent ectopy that further complicates catheter stability.…”
Section: Outcomes Of Catheter Ablationmentioning
confidence: 99%
See 1 more Smart Citation